Changing Landscapes: The Provincial Text in Russian-Soviet Culture. Introduction (ENTHYMEMA, 2022)
Introduction to the monographic section “Changing Landscapes: the Provincial Text in Russian-Soviet Culture.”
Keywords: Geocriticism; Imagined Geography; Provincial Text; Russian-Soviet Culture.